Function of Biohydrogen Metabolism and Related Microbial Communities in Environmental Bioremediation - Teng, Ying; Xu, Yongfeng; Wang, Xiaomi; Christie, Peter (Frontiers in Microbiology, 2019)
Hydrogen (H2) metabolism has attracted considerable interest because the activities of H2-producing and consuming microbes shape the global H2 cycle and may have vital relationships with the global cycling of other elements. There are many pathways of microbial H2 emission and consumption which may affect the structure and function of microbial communities. A wide range of microbial groups employ H2 as an electron donor to catalyze the reduction of pollutants such as organohalides, azo compounds, and trace metals. Syntrophy coupled mutualistic interaction between H2-producing and H2-consuming microorganisms can transfer H2 and be accompanied by the removal of toxic compounds. Moreover, hydrogenases have been gradually recognized to have a key role in the progress of pollutant degradation. This paper reviews recent advances in elucidating role of H2 metabolism involved in syntrophy and hydrogenases in environmental bioremediation. Further investigations should focus on the application of bioenergy in bioremediation to make microbiological H2 metabolism a promising remediation strategy.